2012
DOI: 10.1016/j.neubiorev.2012.02.011
|View full text |Cite
|
Sign up to set email alerts
|

APP transgenic mice for modelling behavioural and psychological symptoms of dementia (BPSD)

Abstract: The discovery of gene mutations responsible for autosomal dominant Alzheimer's disease has enabled researchers to reproduce in transgenic mice several hallmarks of this disorder, notably Aβ accumulation, though in most cases without neurofibrillary tangles. Mice expressing mutated and wild-type APP as well as C-terminal fragments of APP exhibit variations in exploratory activity reminiscent of behavioral and psychological symptoms of Alzeimer dementia (BPSD). In particular, open-field, spontaneous alternation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 328 publications
(551 reference statements)
6
43
0
Order By: Relevance
“…These symptoms may age-dependently occur in transgenic mice (Hsiao et al, 1996;Moechars et al, 1999;Chen et al, 2000). It has been reported that the APP transgenic mice are valuable tools to develop new drugs for dementia and BPSD (Lalonde et al, 2012). The present data indicate that a single injection of Aβ1-42 (500 pmol/mouse) into the lateral ventricle of individually housing adult mice irreversibly induces cognitive decline and BPSD-like symptoms in a few weeks and may be a protocol to prepare a model for BPSD with dementia.…”
Section: Discussionmentioning
confidence: 49%
“…These symptoms may age-dependently occur in transgenic mice (Hsiao et al, 1996;Moechars et al, 1999;Chen et al, 2000). It has been reported that the APP transgenic mice are valuable tools to develop new drugs for dementia and BPSD (Lalonde et al, 2012). The present data indicate that a single injection of Aβ1-42 (500 pmol/mouse) into the lateral ventricle of individually housing adult mice irreversibly induces cognitive decline and BPSD-like symptoms in a few weeks and may be a protocol to prepare a model for BPSD with dementia.…”
Section: Discussionmentioning
confidence: 49%
“…OFT perimeter vertical counts also demonstrated a significant age × genotype interaction, as counts increased with age in APP/PS1/KALRN(+/+) mice while declining in KALRN(+/+), although these changes were not independently significant. Spontaneous Alternation percent correct, which could be seen as a measure of apathetic or perseverative behavior (Lalonde et al, 2012), did not differ between APP/PS1/KALRN(+/+) and KALRN(+/+) mice (data not shown).…”
Section: Resultsmentioning
confidence: 95%
“…A recent comprehensive review concluded that despite some conflicting findings, increased hyperactivity in the open field test with age was the most common pattern in mice transgenic for the APPswe mutation, including in APPswe/PSEN1dE9 mice, suggesting a relationship to accumulation of pathology (Lalonde et al, 2012). APP transgenic mice strains were more variable in demonstrating decreased, increased, or unchanged anxiety/inhibition (Lalonde et al, 2012), although several studies have reported APPswe/PSEN1dE9 mice to evidence disinhibition/reduced anxiety (Dumont et al, 2004; Lalonde et al, 2005; Reiserer et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Although several reviews of murine Alzheimer models have appeared (Van Leuven, 2000; Ashe, 2001; Morgan, 2003; Sant’ Angelo et al, 2003; German and Eisch, 2004; Mineur et al, 2005; Spires and Hyman, 2005; McGowan et al, 2006; Gimenez-Llort et al, 2007; Duyckaerts et al, 2008; Howlett and Richardson, 2009; Kokjohn et al, 2009; Ashe and Zahs, 2010; Wirths and Bayer, 2010; Scearce-Levie, 2011; Lalonde et al, 2012), the authors mostly describe the effects of accumulating Aβ concentrations on synaptic activity or learning abilities in various spatial and non-spatial tasks. We present in-depth task-by-task effects of APP transgenesis on survival and basic neurologic functions regarding pathological reflexes, myoclonus, and epilepsy.…”
Section: Neurologic Symptoms and Survival Rates In App Micementioning
confidence: 99%